1970
DOI: 10.1002/art.1780130302
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin m deficiency in the immune response of patients with rheumatoid arthritis

Abstract: The specific antibody production in patients with rheumatoid arthritis in response to three antigen-heep cell stroma, Brucellin and Limulus polyphemus hemocyanin-was examined. Several antigens were used in expectation that an abnormality in antibody production might be selective and not uniform for all , antigens. Patients with rheumatoid arthritis were deficient in their IgM response to sheep cell stroma and Brucellin, especially the latter. This deficiency was limited to the primary response and to secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…A similar tendency was found with respect to evoked antibody response after challenge with several vaccines. Other studies have reported normal antibody responses (14) or a defect in the M response in patients with rheumatoid arthritis (15). Quite recently, Rawson and Huang (16,17) have reported studies similar in many ways to our own.…”
Section: Discussionsupporting
confidence: 79%
“…A similar tendency was found with respect to evoked antibody response after challenge with several vaccines. Other studies have reported normal antibody responses (14) or a defect in the M response in patients with rheumatoid arthritis (15). Quite recently, Rawson and Huang (16,17) have reported studies similar in many ways to our own.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, low titer of 7s and 19s antibodies to blood groups A and B antigens has been reported in rheumatoid arthritis (40,41). Also selective deficiency of IgM antibody production in response to a weak antigenic stimulus was observed in this disease (42). T h e concentration of immunoglobulins in rheumatoid synovial fluids vary, being either low, equal, or higher than in the corresponding sera (39).…”
Section: Discussionmentioning
confidence: 81%
“…Bandilla also showed that patients with RA have a deficient IgM response to active immunization with keyhole limpet hemocyanin (24). Only after intense stimulation could adequate levels of IgM antibodies be achieved (24). However, patients with SLE develop high titers of IgG isohemagglutin antibody titers in response to injections with incompatible blood group antigens (25).…”
Section: Discussionmentioning
confidence: 99%